ATF4-dependent increase in mitochondrial-endoplasmic reticulum tethering following OPA1 deletion in skeletal muscle. - Hinton, A.; Katti, P.; Mungai, M.; Hall, D.D.; Koval, O.; Shao, J.; Vue, Z.; Lopez, E.G.; Rostami, R.; Neikirk, K.; Ponce, J.; Streeter, J.; et al. (Journal of Cellular Physiology, 2024)
Mitochondria and endoplasmic reticulum (ER) contact sites (MERCs) are protein- and lipid-enriched hubs that mediate interorganellar communication by contributing to the dynamic transfer of Ca[2+], lipid, and other metabolites between these organelles. Defective MERCs are associated with cellular oxidative stress, neurodegenerative disease, and cardiac and skeletal muscle pathology via mechanisms that are poorly understood. We previously demonstrated that skeletal muscle-specific knockdown (KD) of the mitochondrial fusion mediator optic atrophy 1 (OPA1) induced ER stress and correlated with an induction of Mitofusin-2, a known MERC protein. In the present study, we tested the hypothesis that Opa1 downregulation in skeletal muscle cells alters MERC formation by evaluating multiple myocyte systems, including from mice and Drosophila, and in primary myotubes. Our results revealed that OPA1 deficiency induced tighter and more frequent MERCs in concert with a greater abundance of MERC proteins involved in calcium exchange. Additionally, loss of OPA1 increased the expression of activating transcription factor 4 (ATF4), an integrated stress response (ISR) pathway effector. Reducing Atf4 expression prevented the OPA1-loss-induced tightening of MERC structures. OPA1 reduction was associated with decreased mitochondrial and sarcoplasmic reticulum, a specialized form of ER, calcium, which was reversed following ATF4 repression. These data suggest that mitochondrial stress, induced by OPA1 deficiency, regulates skeletal muscle MERC formation in an ATF4-dependent manner.